Platelet mass index can be a reliable marker in predicting the prognosis of retinopathy of prematurity in very preterm infants - Levent Korkmaz; Osman Baştuğ; Ahmet Özdemir; Sabriye Korkut; Çağatay Karaca; Mustafa Ali Akın; Mehmet Adnan Öztürk (Pediatrics and Neonatology)
Background: Retinopathy of prematurity (ROP) is a proliferative vitreoretinopathy resulting from vascular defect of the retina. The present study evaluates platelets, which are involved in VEGF storage, transport and release, and their functions with regard to the prognosis of the disease. The objective was to suggest a simple minimal invasive method that will facilitate the management of the disease and help clinicians in predicting the prognosis. Methods: In this single center, retrospective, case–control study, we included a control group consisting of very preterm newborns (n = 83) at risk of ROP and a laser photocoagulation group including infants (n = 63) who received laser therapy during their follow-up examinations. The employed assessments included platelet counts and platelet mass index (PMI) which provide guidance in understanding platelet activity. In doing so, consideration was given to the first and second phases of ROP. The accuracy of prognostication was assessed with receiver operating characteristic analyses. Results: The study groups did not differ statistically significantly by platelet count during the first and second phases of ROP (p > 0.05) nor were the PMI measurements statistically significantly different between the study groups during the first phase of the disease (p > 0.05). PMI values of the study groups, however, differed significantly in the second phase of ROP (p < 0.05). Conclusion: The present study found a significant difference between the two groups in PMI measurements which reflect increased VEGF levels during the neovascularization phase, which underlies the disease. This conclusion demonstrated that monitoring the PMI values in newborns at risk of ROP can be considered to be a minimally invasive method that by changing the retinal examination procedure in use today which is rather troublesome for both the physician and the newborn, can provide facilities in monitoring the disease for both the physician and the newborn. Key Words: marker in prediction, platelet mass index, prognosis, retinopathy of prematurity